(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This article examines social representations of information and communications technologies (ICT) in high school students in Niamey, Niger, and explores whether these representations are determined by training in and regular use of ICT. A sample of 50 students attending two lycées (an academically oriented high school) was studied. Only one lycée offered computer courses. The results of semi-directed interviews show that, whether or not they took computer courses, the students developed social representations of ICT. These representations were associated with favourable attitudes toward computer and Internet use at school. The chi-square test hypothesis shows that students’ social representations of ICT were not determined by training in ICT.